Determination of Treatment Policy for Acute Surgical Disease of the Abdominal Cavity and Retroperitoneal Space in Patients with Late-Stage HIV Infection According to Multislice Computed Tomography and Magnetic Resonance Imaging Data - N. V. Klimova; A. A. Gaus; V. V. Darvin; U. B. Il'ina (Вестник рентгенологии и радиологии, 2020)
Objective: to determine treatment policy for an acute surgical disease in patients with late-stage HIV infection diagnosed using the data of the highly informative imaging techniques multislice computed tomography (MSCT) and magnetic resonance imaging (MRI). Material and methods. In 2008 and 2016, the authors examined 425 patients (320 men and 105 women) with acquired immunodeficiency syndrome (AIDS) who were treated at the surgical units of the Surgut Regional Clinical Hospital, by using the data of MSCT (Toshiba Aquilion 64, Japan) and MRI (Siemens 1,5T Magnetom Essenza, Germany) in identifying both local surgical and general mixed diseases.Results. Analysis of acute surgical diseases of the abdominal cavity and retroperitoneal space in patients with late-stage HIV infection determined that the treatment policy in this category of patients depended on clinical diagnostic data.Conclusions. 1. MSCT and MRI are highly informative techniques in diagnosing acute surgical diseases in patients with late-stage HIV infection. 2. The course of an acute surgical disease in patients with late-stage HIV infection in the presence of generalized opportunistic infection makes it preferable to perform minimally invasive surgical interventions.